Introduction: International municipalism and the right to the city (contradictions and challenges) - Eva Garcia-Chueca; Raquel Rolnik (Revista CIDOB d'Afers Internacionals, 2019)
This paper presents and contextualises issue 123 of Revista CIDOB d'Afers Internationals on “International municipalism and the right to the city: cities in the age of globalisation”. To do this, it outlines the trajectory of the right to the city, from the streets to the institutional world. While the right to the city has been written about extensively, its incorporation into international municipalism remains little explored in academic literature. This is the added value of the analysis contained in this monograph, the results of which are set out in its seven articles. More than answering established questions, the topics expanded upon here raise new questions and propose a new agenda for research and discussion on the contradictions and challenges of the right to the city, with all that it entails.